DEVELOPMENT OF CONTENT RECOMMENDATION SYSTEMS IN THE FORM OF METADATA-BASED CAROUSEL - Hascaryo Pramudibyanto (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study aims to develop a metadata-based content recommendation system using a Carousel model to support effective communication and promotion at the Universitas Terbuka Service Center (Sentra Layanan Universitas Terbuka/SALUT), particularly at SALUT HEBAT in Semarang City. While prior studies on digital content strategies often emphasize paid advertising or algorithm-driven personalization, limited attention has been given to metadata-based visual approaches in distance education services. The Carousel model was selected because it can present content in a visual and interactive format, thereby enhancing audience engagement and appeal. This research employs a qualitative descriptive method, with data collection techniques including interviews, observations, and documentation of social media activities. A one-month implementation produced encouraging results, with 303 views, 277 likes, and 78 link clicks on SALUT's Instagram content, achieved without paid advertising (Meta Ads). These findings demonstrate that metadata-based content strategies, combined with consistent visual design and clear calls to action, can organically attract audience interest. The study recommends optimizing Meta Ads, providing digital marketing training, developing a dashboard monitoring system, and fostering local collaboration for content dissemination. This research contributes by addressing the gap in sustainable, low-cost digital engagement strategies for distance education services and offering a replicable model for broader.